A Home for Age Studies? - Lamb, Erin (Age, Culture, Humanities: An Interdisciplinary Journal, 2023)
Age studies, particularly within the United States, is academically “homeless.” You cannot get a degree in age studies; you will not find departments of age or aging studies with strong humanities representation; and you will not find job listings seeking experts in age studies. This essay explores some of the consequences that follow from age studies not having an academic “home,” as well as the gains and constraints that age studies scholars may encounter when pursuing age studies work within a different discipline or field, using the particular example of working within health humanities. While the essay ultimately presents ambivalence about the necessity, and pessimism about the practicality, of an academic home for age studies, it does lay out several priorities for future field growth. In particular, the priority that should guide field-building in age studies is enabling future students to pursue work in age studies. Submitted: October 15, 2023 Published: November 19, 2023